Exhibiting Images of Disabled Dancers: Comparison, Reconstruction or Disruption?. (May 2022) - Stamp, Kathryn
Abstract : When People Dancing's 2013 '11 Million Reasons' (11MR) project was first advertised, the vision for the photography exhibition was to 'recreate iconic dance moments in film'. 1 When the 2016 follow-on project '11 Million Reasons to Dance' (11MRTD) was conceptualised, the exhibition's premise was described as commissioning 'images of iconic dance moments from film, all reimagined by Deaf, sight impaired and disabled dancers'. 2 This shift from 'recreated' to 'reimagined', as well as the decision to use a RE approach at all for an intervention, was intriguing. This article explores the meaning, purpose and use of the RE prefix, evaluating its use in dance contexts, its impact when used within disability contexts and its use for the 11MRTD project, as well as considering questions raised by the project regarding the recreation of popular dance scenes in relation to the viewing of non-normative bodies by public audiences.